2016
DOI: 10.1016/j.brs.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation of Left Dorsolateral Prefrontal Cortex Induces Brain Morphological Changes in Regions Associated with a Treatment Resistant Major Depressive Episode: An Exploratory Analysis

Abstract: Background Repetitive transcranial magnetic stimulation (TMS) is an FDA-approved antidepressant treatment but little is known of its mechanism of action. Specifically, downstream effects of TMS remain to be elucidated. Objective/Hypothesis To identify brain structural changes from TMS treatment of a treatment resistant depressive episode through an exploratory analysis Methods 27 subjects in a DSM-IV current major depressive episode and on a stable medication regimen, had a 3T magnetic resonance T1 structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 63 publications
(59 reference statements)
6
55
1
Order By: Relevance
“…Both datasets have been analyzed previously [9,10,31], including a voxel-based morphometry analysis of gray matter density with findings in the rostral anterior cingulate cortex as reported above [7]. Cerebral cortex thickness has not been evaluated previously in either dataset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both datasets have been analyzed previously [9,10,31], including a voxel-based morphometry analysis of gray matter density with findings in the rostral anterior cingulate cortex as reported above [7]. Cerebral cortex thickness has not been evaluated previously in either dataset.…”
Section: Methodsmentioning
confidence: 99%
“…For patients receiving rTMS to the dorsolateral prefrontal cortex (DLPFC) as a treatment for depression, longitudinal studies have shown no global change in brain volume [4], a significant reduction in left hippocampus volume that was driven by the non-responders [5], and a significant increase in hippocampus volume that did not correlate with clinical response [6]. A 2016 study showed a longitudinal increase in gray matter density in several brain areas over a course of rTMS for depression and a single region, the rostral anterior cingulate cortex (rACC) extending into medial prefrontal cortex, with increased gray matter density that correlated with clinical improvement [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four regions in which they detect these changes were: left anterior cingulate cortex, the left insula, left superior temporal gyrus and the right angular gyrus. Increase in the volume of the left anterior cingulate cortex correlated with improvement of depression severity (Lan et al 2016). …”
Section: Introductionmentioning
confidence: 98%
“…It is believed that rTMS over the DLPFC modulates brain network involved in the regulation of mood and affects various neurotransmitters. Lan and colleagues (2016) described the structural changes in the brain (gray matter volume increased by 3.5-11.2%) in patients with a depressive disorder after rTMS treatment (Lan et al 2016). Four regions in which they detect these changes were: left anterior cingulate cortex, the left insula, left superior temporal gyrus and the right angular gyrus.…”
Section: Introductionmentioning
confidence: 99%